Multi-stage copolymer for powder coating, its production method, and powder coating composition

A multi-stage copolymer for powder coatings, composed of specific polymer components and produced through emulsion polymerization, addresses the challenge of achieving both appearance and toughness in thick films, resulting in a durable and smooth coating film with low viscosity.

JP7616221B2Active Publication Date: 2025-01-17MITSUBISHI CHEM CORP

Patent Information

Application Number
JP2022534015
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-29
Filing Date
2021-06-29
Publication Date
2025-01-17
Estimated Expiration
2041-06-29

AI Technical Summary

Technical Problem

Existing powder coatings face challenges in achieving both good appearance and excellent toughness, particularly when applied as thick films, and there is a need for improved dispersibility and reduced melt viscosity of multistage polymer particles in thermoplastic resins.

Method used

A multi-stage copolymer for powder coatings composed of three polymer components with specific glass transition temperatures and monomer compositions, combined with a thermoplastic resin, is developed, allowing for a coating film with enhanced appearance and toughness. The copolymer is produced through a method involving emulsion polymerization and spray-drying to achieve optimal particle sizes and distribution.

Benefits of technology

The multi-stage copolymer provides a coating film with excellent toughness and appearance, while maintaining low melt viscosity, suitable for forming smooth and durable films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616221000004
    Figure 0007616221000004
  • Figure 0007616221000001
    Figure 0007616221000001
  • Figure 0007616221000002
    Figure 0007616221000002
Patent Text Reader

Abstract

A multistage copolymer for powder coating materials which is configured of at least three polymer components, the three polymer components being a first-stage polymer (A), a second-stage polymer (B), and a third-stage polymer (C). The polymer (A) has a glass transition temperature of -15°C or higher, the polymer (B) has a glass transition temperature of -20°C or lower, and the polymer (C) has a glass transition temperature of 60°C or higher. The multistage copolymer for powder coating materials contains the polymer (A) in an amount of 1-30 mass% with respect to the whole multistage copolymer, which is taken as 100 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multistage copolymer for powder coatings and a method for producing the same, as well as a powder coating composition containing the multistage copolymer for powder coatings. This application claims priority based on Japanese Patent Application No. 2020-111778, filed on June 29, 2020, the contents of which are incorporated herein by reference. [Background technology]

[0002] In recent years, powder coatings have been used in a wide range of fields because they do not generate organic solvents when the coating film is baked, are organic solvent-free and therefore are excellent for the working environment, and are non-hazardous and resource-saving.

[0003] Powder coatings are characterized by being solvent-free and capable of forming a thick film of 30 to 100 μm in one coat, in comparison with solvent-based coatings. On the other hand, powder coatings have problems such as a decrease in workability of the coating film due to the thick coating film obtained by coating. Conventionally, polyester-based powder coatings have been widely used for outdoor applications such as road materials and building materials. In recent years, polyester-based powder coatings with even higher weather resistance have been studied from the viewpoint of maintenance-free. There is an increasing demand for improving the toughness of the coating film obtained from these polyester-based powder coatings with higher weather resistance.

[0004] For example, Patent Document 1 discloses an example of applying a multi-layer polymer obtained by graft-polymerizing a vinyl monomer onto a rubber-like polymer to a powder coating. Patent Document 1 discloses that the processability and impact resistance of a coating film can be improved by dispersing a multi-stage copolymer having a polymer layer with a glass transition temperature of 20° C. or less and a polymer layer with a glass transition temperature of 60° C. or more in a powder coating. However, there is a demand for the development of a powder coating that can provide a coating film with further improved toughness.

[0005] In addition, it has been known that multi-layer polymer particles (multi-stage polymers) are blended with thermoplastic resins to improve impact resistance. Patent Documents 2 to 4 disclose examples of applying multi-layer polymer particles as impact resistance modifiers. In detail, Patent Documents 2 to 4 disclose a technique for improving impact resistance, temperature dependency of haze, impact whitening resistance, etc., by adding a multi-stage polymer having a basic structure of three layers of hard-soft-hard to a hard resin such as a methacrylic resin. However, since the above technique is related to application to resin materials for molding parts, when the above technique is applied to powder coatings, the dispersibility of the multi-stage polymer in the thermoplastic resin is insufficient. In addition, the melt viscosity of a powder coating composition containing a multi-stage polymer tends to increase, so the appearance and toughness of the coating film obtained from the powder coating composition are insufficient. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2000-1633 A [Patent Document 2] Japanese Unexamined Patent Publication No. 48-55233 [Patent Document 3] Japanese Patent Application Publication No. 10-338723 [Patent Document 4] International Publication No. 2005 / 095480 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a multi-stage copolymer for powder paint which can give a coating film having good appearance and excellent toughness, a method for producing the same, and a powder coating composition containing the multi-stage copolymer for powder paint. [Means for solving the problem]

[0008] The present invention has the following aspects. [1] A multi-stage copolymer for powder coating, comprising at least three polymer components: a first stage polymer (A), a second stage polymer (B), and a third stage polymer (C), a multistage copolymer for powder coating, the polymer (A) having a glass transition temperature of -15°C or higher, the polymer (B) having a glass transition temperature of -20°C or lower, and the polymer (C) having a glass transition temperature of 60°C or higher, the multistage copolymer for powder coating containing the polymer (A) in an amount of 1% by mass or more and 30% by mass or less when the total amount of the multistage copolymer for powder coating is taken as 100% by mass; and a thermoplastic resin which is a polyester. . [2] A multi-stage copolymer for powder coating, comprising at least an inner layer, an intermediate layer, and an outer layer, The inner layer contains a polymer (A) having a glass transition temperature of -15°C or higher, the intermediate layer comprises a polymer (B) having a glass transition temperature of −20° C. or lower, the outer layer comprises a polymer (C) having a glass transition temperature of 60° C. or higher, A multi-stage copolymer for powder coating, containing the polymer (A) in an amount of 2% by mass or more and 20% by mass or less, when the total amount of the multi-stage copolymer for powder coating is taken as 100% by mass. and a thermoplastic resin which is a polyester. . [3] The polymer (B) obtained by polymerizing a monomer mixture in the presence of the polymer (A), and the polymer (C) obtained by polymerizing a monomer mixture in the presence of a polymer containing the polymer (A) and the polymer (B), according to [1] or [2]. powder coating composition . [4] A multi-stage copolymer for powder coating, comprising at least three polymer components: a polymer (A), a polymer (B), and a polymer (C), 3. The multi-stage copolymer for powder coating according to claim 1 or 2, wherein at least two peaks are present in a tan δ curve between −60° C. and 140° C. in a temperature dispersion measurement of dynamic viscoelasticity of the multi-stage copolymer for powder coating. and a thermoplastic resin which is a polyester. . [5] The polymer (A) according to any one of [1] to [4], wherein the polymer (A) contains 35% by mass or more and 99.5% by mass or less of methyl methacrylate units and 0.5% by mass or more and 5% by mass or less of a polyfunctional monomer, when the total amount of monomer units in the polymer (A) is taken as 100% by mass. powder coating composition. [6] The polymer (B) according to any one of [1] to [5], wherein the polymer (B) contains 70% by mass or more and 99.5% by mass or less of alkyl (meth)acrylate units having an alkyl group with a carbon number of 4 to 8, and 0.5% by mass or more and 5% by mass or less of a polyfunctional monomer, when the total amount of monomer units in the polymer (B) is taken as 100% by mass. powder coating composition . [7] The polymer (C) according to any one of [1] to [6], wherein the polymer (C) contains 70% by mass or more and 100% by mass or less of methyl methacrylate units, when the total amount of monomer units in the polymer (C) is taken as 100% by mass. powder coating composition . [8] The particle according to any one of [1] to [7], wherein the volume average particle size of the primary particles is 0.1 μm or more and 10 μm or less. powder coating composition . [9] The particle according to any one of [1] to [8], wherein the volume average particle size of the secondary particles is 1 μm or more and 500 μm or less. powder coating composition .

[10] The composition according to any one of [1] to [9], wherein, when the total of the polymer (A), the polymer (B), and the polymer (C) is taken as 100 mass%, the composition contains the polymer (A) in an amount of 1 mass% or more and 30 mass% or less, the polymer (B) in an amount of 31 mass% or more and 94 mass% or less, and the polymer (C) in an amount of 5 mass% or more and 39 mass% or less. powder coating composition If.

[11] Any of the items described in [1] to

[10] powder coating composition A method for producing a step (1) of polymerizing a first monomer mixture for constituting a polymer (A) to obtain a first dispersion containing the polymer (A), then adding a second monomer mixture for constituting a polymer (B) dropwise to the first dispersion to polymerize the second monomer mixture to obtain a second dispersion containing the polymer (A) and the polymer (B), and further adding a third monomer mixture for constituting a polymer (C) dropwise to the second dispersion to polymerize the third monomer mixture to obtain a third dispersion containing a multistage copolymer containing the polymer (A), the polymer (B), and the polymer (C); and (2) spray-drying the third dispersion to obtain a powder containing the multistage copolymer. powder coating composition Manufacturing method 。

[12] When the total amount of the powder coating composition is taken as 100 mass%, the content of the multi-stage copolymer for powder coating is 1 mass% or more and 20 mass% or less. [ 1 ] ~ [ 10 ] Either 13. The powder coating composition according to claim 12. Effect of the Invention

[0009] According to the present invention, it is possible to provide a multistage copolymer for powder paint which can give a coating film having good appearance and excellent toughness, a method for producing the same, and a powder coating composition containing the multistage copolymer for powder paint. [Brief description of the drawings]

[0010] [Figure 1] FIG. 2 is a graph showing a tan δ curve in the range of −60° C. to 140° C. calculated by measuring the temperature dispersion of the dynamic viscoelasticity of the multistage copolymer in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the multistage copolymer for powder paint and the production method thereof, as well as the powder paint composition containing the multistage copolymer for powder paint according to the present invention will be described.

[0012] [Multi-stage copolymer for powder coating] The multi-stage copolymer for powder coating according to an embodiment of the present invention (hereinafter referred to as "this embodiment") is composed of at least three polymer components: a first stage polymer (A), a second stage polymer (B), and a third stage polymer (C), in which the glass transition temperature of polymer (A) is -15°C or higher, the glass transition temperature of polymer (B) is -20°C or lower, and the glass transition temperature of polymer (C) is 60°C or higher, and when the total amount of the multi-stage copolymer for powder coating is taken as 100% by mass, the copolymer contains 1% by mass or more and 30% by mass or less of polymer (A).

[0013] The glass transition temperature (hereinafter also referred to as "Tg") is a value calculated from the following FOX formula (Formula (1)). In this specification, the unit of Tg is "°C". Specifically, in the case of a polymer (homopolymer) consisting of only a single monomer, standard analytical values ​​described in "Polymer Data Handbook" compiled by the Society of Polymer Science and the like can be adopted, and in the case of a copolymer obtained by polymerizing n (n is a natural number of 2 or more) types of monomers, it can be calculated from the Tg of the homopolymer of each monomer using the following formula (1). Table 1 shows literature values ​​of Tg of representative homopolymers.

[0014] 1 / (273+Tg)=Σ(Wn / (273+Tgn)) (1) In the formula, Wn represents the mass fraction of monomer n, and Tgn represents the glass transition temperature (°C) of a homopolymer of monomer n. Here, the mass fraction is the ratio of the amount of monomer n charged to the total amount of all monomers charged.

[0015] [Table 1]

[0016] The abbreviations in Table 1 represent the following monomers. "MMA": Methyl methacrylate "EMA": Ethyl methacrylate "n-BMA": n-butyl methacrylate - "i-BMA": i-butyl methacrylate - "t-BMA": t-butyl methacrylate "n-HMA": n-hexyl methacrylate 2-EHMA: 2-ethylhexyl methacrylate "MA": Methyl acrylate "EA": Ethyl acrylate "n-BA": n-butyl acrylate "n-HA": n-hexyl acrylate 2-EHA: 2-ethylhexyl acrylate "MAA": Methacrylic acid 2-HEMA: 2-hydroxyethyl methacrylate

[0017] For homopolymers whose glass transition temperature is not described in the literature, the glass transition temperature can be determined by measurement. In this case, the Tg of the homopolymer may be measured using a known method such as differential scanning calorimetry, thermomechanical analysis, or dynamic viscoelasticity measurement. For multistage copolymers or resin compositions containing multistage copolymers, even if the Tg cannot be calculated using the above formula (1), the Tg may be measured by the above method.

[0018] The Tg of the polymer (A) is −15° C. or higher, and preferably 0° C. or higher. When the Tg of the polymer (A) is −15° C. or higher, it is possible to obtain a multistage copolymer that can provide a powder coating composition capable of forming a coating film excellent in toughness and appearance.

[0019] The Tg of the polymer (B) is −20° C. or lower, and preferably −40° C. or lower. When the Tg of the polymer (B) is −20° C. or lower, it is possible to obtain a multistage copolymer that can provide a powder coating composition capable of forming a coating film having excellent toughness.

[0020] The Tg of the polymer (C) is 60° C. or higher, and preferably 80° C. or higher. When the Tg of the polymer (C) is 60° C. or higher, the multistage copolymer is well dispersed in the thermoplastic resin, so that a multistage copolymer can be obtained that can provide a powder coating composition capable of forming a coating film with excellent appearance.

[0021] Another multistage copolymer for powder coating of the present invention is composed of at least three polymer components, polymer (A), polymer (B), and polymer (C), and in a temperature dispersion measurement of dynamic viscoelasticity of the multistage copolymer for powder coating, at least two peaks are present in a tan δ curve between -60°C and 140°C. When there are at least two peaks in the tan δ curve, it is possible to obtain a multistage copolymer for powder coating that can provide a powder coating composition capable of forming a coating film excellent in toughness and appearance.

[0022] Of the at least two peaks present in the tan δ curve, the peak on the low temperature side is preferably present at -60°C to 15°C, more preferably at -60°C to 5°C, and even more preferably at -60°C to -5°C. The peak on the high temperature side is preferably present at 60°C to 140°C, more preferably at 70°C to 140°C, and even more preferably at 80°C to 140°C. When at least two peaks present in the tan δ curve are within the above ranges, a multistage copolymer for powder coating can be obtained, which can provide a powder coating composition capable of forming a coating film excellent in toughness and appearance.

[0023] The dynamic viscoelasticity of the multistage copolymer for powder coating can be measured by a known method. In this embodiment, the dynamic viscoelasticity was measured by using a viscoelasticity measuring device DMA6100 (manufactured by Hitachi High-Tech Science Corporation) to calculate a tan δ curve by measuring a film-like test piece of the multistage copolymer for powder coating, which was prepared by press molding in a press molding machine under conditions of 180°C and 3 MPa for 10 minutes, in a measurement bending mode, at a frequency of 1 Hz, in the range of -100°C to 150°C.

[0024] "Composition of polymer (A), polymer (B) and polymer (C)" The compositions of polymer (A), polymer (B) and polymer (C) constituting the multistage copolymer for powder coating of this embodiment are as follows.

[0025] When the total amount of monomer units constituting polymer (A) is taken as 100 mass%, polymer (A) preferably contains 35 mass% or more and 99.5 mass% or less of methyl methacrylate units and 0.5 mass% or more and 5 mass% or less of polyfunctional monomer units, more preferably contains 40 mass% or more and 99.5 mass% or less of methyl methacrylate units and 0.5 mass% or more and 5 mass% or less of polyfunctional monomer units, and even more preferably contains 45 mass% or more and 99.5 mass% or less of methyl methacrylate units and 0.5 mass% or more and 5 mass% or less of polyfunctional monomer units. When the polymer (A) contains 35% by mass or more and 99.5% by mass or less of methyl methacrylate units, it is possible to obtain a multistage copolymer that can provide a powder coating composition capable of forming a coating film excellent in toughness and appearance.

[0026] When the polymer (A) contains 0.5% by mass or more of the polyfunctional monomer unit, the multistage copolymer is well dispersed in the thermoplastic resin, and therefore a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent appearance can be obtained.When the polymer (A) contains 5% by mass or less of the polyfunctional monomer unit, a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent toughness can be obtained.

[0027] The monomer forming the polyfunctional monomer unit is a monomer having at least two or more polymerizable groups in the molecule, and examples thereof include unsaturated carboxylic acid allyl esters such as allyl acrylate, allyl methacrylate, diallyl maleate, diallyl fumarate, and diaryl itaconate, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol dimethacrylate, divinylbenzene, etc. One of these monomers may be used alone, or two or more of them may be used in combination.

[0028] When the total amount of monomer units constituting polymer (B) is taken as 100 mass%, polymer (B) preferably contains 70 mass% or more and 99.5 mass% or less of alkyl (meth)acrylate units in which the alkyl group has 4 to 8 carbon atoms and 0.5 mass% or more and 5 mass% or less of polyfunctional monomer units, and more preferably contains 85 mass% or more and 99.5 mass% or less of alkyl (meth)acrylate units in which the alkyl group has 4 to 8 carbon atoms and 0.5 mass% or more and 5 mass% or less of polyfunctional monomer units. When polymer (B) contains 70% by mass or more and 99.5% by mass or less of alkyl (meth)acrylate units in which the alkyl group has 4 to 8 carbon atoms, a multistage copolymer can be obtained that can provide a powder coating composition capable of forming a coating film with excellent toughness.

[0029] When the polymer (B) contains 0.5% by mass or more of the polyfunctional monomer unit, the multistage copolymer is well dispersed in the thermoplastic resin, and therefore a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent appearance can be obtained.When the polymer (B) contains 5% by mass or less of the polyfunctional monomer unit, a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent toughness can be obtained.

[0030] Examples of monomers forming alkyl (meth)acrylate units in which the alkyl group has 4 to 8 carbon atoms include (meth)acrylic acid esters such as n-butyl (meth)acrylate, s-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These (meth)acrylic acid esters may be used alone or in combination of two or more. It should be noted that "(meth)acrylate" is a general term for acrylate and methacrylate, and "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid.

[0031] In the polymer (B), examples of the monomer that forms the polyfunctional monomer unit include the monomers that form the polyfunctional monomer unit in the above polymer (A).

[0032] Polymer (C) preferably contains 70% by mass or more and 100% by mass or less of methyl methacrylate units, and more preferably contains 70% by mass or more and 99.5% by mass or less, when the total amount of monomer units constituting polymer (C) is taken as 100% by mass. When polymer (C) contains 70% by mass or more and 100% by mass or less of methyl methacrylate units, the dispersion of the multistage copolymer in the thermoplastic resin is good, so that a multistage copolymer can be obtained that can provide a powder coating composition capable of forming a coating film with excellent appearance.

[0033] It is preferable that the polymer (C) contains a multi-stage copolymer that can provide a powder coating composition capable of forming a coating film having excellent appearance due to good dispersion of the multi-stage copolymer in the thermoplastic resin. Examples of the multi-functional monomer unit include monomers that form the multi-functional monomer units in the above polymer (A).

[0034] The polymer (C) may contain a reactive group-containing monomer unit. The monomer forming the reactive group-containing monomer unit is a polymerizable monomer having a functional group in its molecule that can react with the thermoplastic resin or curing agent that constitutes the powder coating composition. Examples of the functional group include a hydroxyl group, a carboxyl group, and an epoxy group. Examples of polymerizable monomers having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate. Examples of polymerizable monomers having a carboxyl group include methacrylic acid and acrylic acid. Examples of polymerizable monomers having an epoxy group include glycidyl (meth)acrylate. When the polymer (C) contains a reactive group-containing monomer unit, the dispersion of the multi-stage copolymer in the thermoplastic resin is improved, so that a multi-stage copolymer that can provide a powder coating composition capable of forming a coating film with excellent appearance can be obtained. In addition, since the polymer (C) contains a reactive group-containing monomer unit, it can react with the thermoplastic resin or curing agent constituting the powder coating composition, and therefore a multi-stage copolymer can be obtained that can provide a powder coating composition capable of forming a coating film with excellent toughness. The reactive group-containing monomer unit is preferably a monomer unit formed from a polymerizable monomer having at least one of a hydroxyl group, a carboxyl group, and an epoxy group.

[0035] When the total amount of monomer units constituting polymer (C) is taken as 100 mass%, polymer (C) preferably contains 70 mass% or more and 100 mass% or less of methyl methacrylate units, and more preferably contains 70 mass% or more and 99.5 mass% or less of methyl methacrylate units and 0.5 mass% or more and 5 mass% or less of polyfunctional monomer units. When the polymer (C) contains 0.5% by mass or more of the polyfunctional monomer unit, the multistage copolymer is well dispersed in the thermoplastic resin, and therefore a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent appearance can be obtained.When the polymer (C) contains 5% by mass or less of the polyfunctional monomer unit, a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent toughness can be obtained.

[0036] The polymer (A), the polymer (B) and the polymer (C) may contain a monomer unit other than the monomer unit. The monomer forming the monomer unit other than the monomer unit (hereinafter also referred to as "other monomer") is not particularly limited as long as it is radically polymerizable, and examples thereof include methyl methacrylate, (meth)acrylate compounds other than the monomer forming the reactive group-containing monomer unit, aromatic vinyl compounds, vinyl cyanide compounds, etc. Examples of the aromatic vinyl compounds include styrene, α-methylstyrene, p-methylstyrene, etc. Examples of the vinyl cyanide compounds include acrylonitrile, methacrylonitrile, etc. These other monomers may be used alone or in combination of two or more.

[0037] "Volume average particle size of primary particles" The multistage copolymer for powder coating of this embodiment preferably has a volume average particle size of its primary particles of 0.1 μm or more and 10 μm or less, more preferably 0.3 μm or more and 3 μm or less, and even more preferably 0.4 μm or more and 1 μm or less. Here, the primary particle refers to the smallest unit of polymer particles constituting the powder containing the multistage copolymer recovered as a powder from the multistage copolymer. If the volume average particle diameter of the primary particles is 0.1 μm or more, it is possible to obtain a multistage copolymer that can provide a powder coating composition capable of suppressing the increase in viscosity during melting of the powder coating composition and forming a coating film with excellent appearance. If the volume average particle diameter of the primary particles is 10 μm or less, it is possible to obtain a multistage copolymer that can provide a powder coating composition capable of forming a coating film with excellent toughness.

[0038] The volume average particle size of the primary particles of the multistage copolymer can be measured by a known method, for example, a laser diffraction method (laser diffraction / scattering method). In the present embodiment, the volume average particle size of the primary particles is a value obtained by measuring and averaging the primary particle sizes of the multistage polymer (dispersed particles) in a dispersion liquid containing the multistage copolymer using a laser diffraction / scattering type particle size distribution measuring device (product name: LA-960, manufactured by Horiba, Ltd.).

[0039] "Volume average particle size of secondary particles" The multistage copolymer for powder coating of this embodiment preferably has a volume average particle size of its secondary particles of 1 μm or more and 500 μm or less, more preferably 1 μm or more and 300 μm or less, and even more preferably 1 μm or more and 100 μm or less. Here, the secondary particles refer to a powder containing the multistage copolymer recovered as a powder. If the volume average particle diameter of the secondary particles is 1 μm or more, dusting and the like can be suppressed, and the powder can be easily handled. If the volume average particle diameter of the secondary particles is 500 μm or less, the dispersibility with the components constituting the powder coating is good, and a multistage copolymer that can provide a powder coating composition capable of forming a coating film with excellent appearance can be obtained.

[0040] The volume average particle size of the secondary particles of the multistage copolymer can be measured by a known method, such as a laser diffraction method (laser diffraction / scattering method), in the same manner as the volume average particle size of the primary particles. In this embodiment, the volume average particle size of the secondary particles is a value obtained by measuring and averaging the secondary particle sizes of the multistage polymer (dispersed particles) in a dispersion liquid containing the multistage copolymer using a laser diffraction / scattering type particle size distribution measuring device (product name: LA-960, manufactured by Horiba, Ltd.).

[0041] "Multi-stage copolymer for powder coatings" The multistage copolymer for powder coating of this embodiment preferably contains polymer (B) obtained by polymerizing a monomer mixture in the presence of polymer (A), and polymer (C) obtained by polymerizing a monomer mixture in the presence of a polymer containing polymer (A) and polymer (B). This makes it possible to obtain a multistage copolymer that can provide a powder coating composition capable of forming a coating film excellent in appearance and toughness. As the monomers which become the monomer units constituting each of the polymer (A), the polymer (B) and the polymer (C), those mentioned above can be used.

[0042] The multistage copolymer for powder coating of this embodiment preferably contains 1 mass% or more and 30 mass% or less of polymer (A), 31 mass% or more and 94 mass% or less of polymer (B), and 5 mass% or more and 39 mass% or less of polymer (C), when the total of polymer (A), polymer (B), and polymer (C) is 100 mass%. When the content of polymer (A) is in the range of 1% by mass or more and 30% by mass or less, a multistage copolymer can be obtained that can provide a powder coating composition capable of forming a coating film excellent in toughness and appearance. When the content of polymer (B) is 31% by mass or more and 94% by mass or less, it is possible to obtain a multistage copolymer which can provide a powder coating composition capable of forming a coating film having excellent toughness. If the content of polymer (C) is 5% by mass or more, the multistage copolymer is well dispersed in the thermoplastic resin, so that a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent appearance can be obtained.If the content of polymer (C) is 39% by mass or less, a multistage copolymer capable of providing a powder coating composition capable of forming a coating film with excellent toughness can be obtained. From the viewpoint of achieving both toughness and appearance of the coating film, the multi-stage copolymer for powder coating of this embodiment preferably contains 2% by mass or more and 20% by mass or less of polymer (A), 45% by mass or more and 93% by mass or less of polymer (B), and 5% by mass or more and 35% by mass or less of polymer (C), and even more preferably contains 3% by mass or more and 15% by mass or less of polymer (A), 50% by mass or more and 93% by mass or less of polymer (B), and 5% by mass or more and 35% by mass or less of polymer (C).

[0043] Another embodiment of the multi-stage copolymer for powder coating of the present invention is a multi-stage copolymer for powder coating comprising at least an inner layer, an intermediate layer and an outer layer, the inner layer containing a polymer (A) having a glass transition temperature of -15°C or higher, the intermediate layer containing a polymer (B) having a glass transition temperature of -20°C or lower, and the outer layer containing a polymer (C) having a glass transition temperature of 60°C or higher. The intermediate layer is present outside the inner layer, and the outer layer is present outside the intermediate layer. The polymer constituting the multi-stage copolymer may contain a polymer other than the polymer (A), the polymer (B) and the polymer (C) (hereinafter, also referred to as "other polymer"). In this case, the other polymer may be present inside the polymer (A), inside the polymer (B), outside the polymer (B), or outside the polymer (C). Other polymers can be used within the range that does not impair the function of the multistage copolymer for powder coating of this embodiment. When the total amount of polymers constituting the multistage copolymer for powder coating of this embodiment is taken as 100 mass%, the content of other polymers is preferably 20 mass% or less.

[0044] According to the multi-stage copolymer for powder coating of this embodiment, the multi-stage copolymer for powder coating is composed of at least three polymer components, the first stage polymer (A), the second stage polymer (B), and the third stage polymer (C), the glass transition temperature of the polymer (A) is -15°C or higher, the glass transition temperature of the polymer (B) is -20°C or lower, and the glass transition temperature of the polymer (C) is 60°C or higher, and when the total amount of the multi-stage copolymer for powder coating is taken as 100% by mass, the multi-stage copolymer contains 1% by mass or more and 30% by mass or less of the polymer (A), so that it is possible to provide a multi-stage copolymer that can provide a powder coating composition capable of forming a coating film having good appearance and excellent toughness. Note that, as long as the order of the first stage, the second stage, and the third stage is maintained, other polymer components may be composed before or after the first stage, after the second stage, or after the third stage.

[0045] The description in this specification regarding the powder coating composition of the present embodiment can also be applied to the powder coating compositions of the other embodiments of the present invention.

[0046] [Method of manufacturing multi-stage copolymers for powder coatings] The method for producing a multistage copolymer for powder paint of this embodiment includes the steps of: polymerizing a first monomer mixture for constituting polymer (A) to obtain a first dispersion containing polymer (A); then adding a second monomer mixture for constituting polymer (B) dropwise to the first dispersion to polymerize the second monomer mixture to obtain a second dispersion containing polymer (A) and polymer (B); and further adding a third monomer mixture for constituting polymer (C) dropwise to the second dispersion to polymerize the third monomer mixture to obtain a third dispersion containing a multistage copolymer containing polymer (A), polymer (B) and polymer (C); and spray-drying the third dispersion to obtain a powder containing the multistage copolymer.

[0047] The multistage copolymer for powder paint of this embodiment can be produced, for example, by a known emulsion polymerization method. A suitable example of the method for producing the multistage copolymer for powder paint of this embodiment is shown below, but the method for producing the multistage copolymer for powder paint of this embodiment is not limited thereto. Here, an example in which emulsion polymerization is used in step (1) is shown.

[0048] Step (1) includes a step (1-1) of polymerizing a first monomer mixture for constituting polymer (A) to obtain a first dispersion containing polymer (A), a step (1-2) of adding a second monomer mixture for constituting polymer (B) dropwise to the first dispersion to polymerize the second monomer mixture to obtain a second dispersion containing polymer (A) and polymer (B), and a step (1-3) of adding a third monomer mixture for constituting polymer (C) dropwise to the second dispersion to polymerize the third monomer mixture to obtain a third dispersion containing a multistage copolymer containing polymer (A), polymer (B), and polymer (C).

[0049] (Process (1-1)) In the step (1-1), deionized water and, if necessary, an emulsifier are added to a reaction vessel, and then a first monomer mixture containing monomers for constituting the polymer (A) is added to polymerize the first monomer mixture to obtain a first latex (first dispersion) containing first dispersed particles made of the polymer (A).

[0050] (Process (1-2)) In step (1-2), a second monomer mixture containing a monomer for constituting polymer (B) is dropped into the first latex (first dispersion) to polymerize the second monomer mixture, thereby obtaining a second latex (second dispersion) containing second dispersed particles consisting of polymer (A) and polymer (B). The second dispersed particles are polymers with a two-layer structure in which the first layer (inner layer) consists of polymer (A) and the second layer (outer layer) consists of polymer (B).

[0051] (Process (1-3)) In step (1-3), a third monomer mixture containing a monomer for constituting polymer (C) is dropped into the second latex (second dispersion) to polymerize the third monomer mixture, thereby obtaining a third latex (third dispersion) containing a multistage copolymer (third dispersed particles) containing polymer (A), polymer (B) and polymer (C). The multistage copolymer is a three-layer polymer in which the first stage (inner layer) is made of polymer (A), the second stage (middle layer) is made of polymer (B), and the third stage (outer layer) is made of polymer (C).

[0052] The emulsion polymerization uses a radical polymerization initiator and an emulsifier. The radical polymerization initiator is not particularly limited, but examples thereof include peroxides, azo-based initiators, and redox-based initiators that combine an oxidizing agent and a reducing agent. The emulsifier is not particularly limited, but is preferably, for example, various carboxylates such as sodium sulfonate, sodium sarcosinate, potassium fatty acid, sodium fatty acid, dipotassium alkenyl succinate, and rosin acid soap, because they have excellent stability of the latex during radical polymerization and can increase the polymerization rate.

[0053] The polymerization temperature in the emulsion polymerization varies depending on the type and amount of the radical polymerization initiator, but is preferably from 40° C. to 120° C., and more preferably from 60° C. to 95° C. The radical polymerization initiator is added to at least one of the aqueous phase and the monomer phase.

[0054] (Process (2)) The multi-stage copolymer obtained by emulsion polymerization is usually in the form of a latex, and therefore in step (2), the multi-stage copolymer is recovered from the latex (third latex) of the multi-stage copolymer obtained in step (1). In step (2), examples of the method for recovering the multistage copolymer from the latex of the multistage copolymer include a wet method in which the latex of the multistage copolymer is coagulated into a slurry by introducing it into hot water in which a coagulant is dissolved, and a spray drying method in which the latex of the multistage copolymer is sprayed into a heated atmosphere to recover a powder containing the multistage copolymer by spray drying. The aggregated particles obtained by the spray drying method are not strongly bonded to each other among the primary particles, so that it is difficult to form a higher-order particle structure, and the primary particles can be uniformly dispersed and directly recovered. Therefore, the spray drying method is preferred as a recovery method.

[0055] The method for producing a multi-stage copolymer for powder coating of this embodiment includes the above-mentioned steps (1) and (2), and therefore can provide a multi-stage copolymer that can provide a powder coating composition capable of forming a coating film having good appearance and excellent toughness.

[0056] [Powder coating composition] The powder coating composition of the present embodiment contains the above-mentioned multi-stage copolymer for powder coating and a thermoplastic resin.

[0057] Examples of the thermoplastic resin include polyester, epoxy resin, acrylic resin, etc. Among these, polyester is preferred from the viewpoints of toughness, appearance, light resistance, and cost of the powder coating composition containing the thermoplastic resin.

[0058] When the powder coating composition of this embodiment contains polyester as a thermoplastic resin, it becomes a polyester-based powder coating. When the powder coating composition of this embodiment contains polyester and epoxy resin as basic components, it becomes a polyester-epoxy hybrid powder coating. When the powder coating composition of this embodiment contains acrylic resin as a basic component, it becomes an acrylic powder coating. Furthermore, when the powder coating composition of this embodiment contains epoxy resin as a basic component, it becomes an epoxy powder coating.

[0059] The polyester is not particularly limited as long as it is used as a polyester powder coating by those skilled in the art. For example, polyester resins having two or more hydroxyl groups or acid groups in one molecule and a softening point in the range of 60°C to 150°C are commonly used as thermoplastic resins.

[0060] The epoxy resin is not particularly limited as long as it is one that is used as an epoxy powder coating by those skilled in the art. Those having an average of about two or more epoxy groups in one molecule are generally used, and examples thereof include bisphenol A epoxy resin, bisphenol B epoxy resin, bisphenol F epoxy resin, novolac type epoxy resin, brominated epoxy resin, alicyclic epoxy resin, etc.

[0061] The acrylic resin is not particularly limited as long as it is used as an acrylic powder coating by those skilled in the art. For example, a (meth)acrylic acid ester copolymer having a softening point of 60°C to 150°C, which is synthesized by copolymerization of a (meth)acrylic acid ester monomer and a (meth)acrylic acid ester monomer having a glycidyl group in the molecule, is generally used as a thermoplastic resin.

[0062] In the powder coating composition of this embodiment, when the total amount of the powder coating composition is taken as 100 mass%, the content of the multi-stage copolymer for powder coating is preferably 1 mass% or more and 20 mass% or less, more preferably 1 mass% or more and 15 mass% or less, and even more preferably 1 mass% or more and 10 mass% or less. If the content of the multistage copolymer for powder coating is 1% by mass or more, a powder coating composition capable of forming a good coating film with excellent toughness can be provided.If the content of the multistage copolymer for powder coating is 20% by mass or less, an increase in the melt viscosity of the powder coating composition can be suppressed, and a powder coating composition capable of forming a smooth coating film can be provided.

[0063] The powder coating composition of this embodiment may contain a curing agent, a pigment, and various other additives in addition to the above-mentioned multistage copolymer for powder coating and thermoplastic resin.

[0064] The powder coating composition of this embodiment can be generally produced by a known method, i.e., by dry-mixing the multi-stage copolymer for powder coating, the thermoplastic resin, and optionally a curing agent, a pigment, and other additives, melt-kneading the mixture at a temperature equal to or higher than the softening point of the thermoplastic resin, and then pulverizing and classifying the mixture as required. Examples of other additives include known additives used in ordinary powder coating compositions, such as surface conditioners, ultraviolet absorbers, antioxidants, and anti-popping agents.

[0065] In dry mixing of the powder coating composition, various mixers such as a Henschel mixer, a Banbury mixer, a high-speed mixer, or a Nauta mixer can be used. Apparatuses used for melt-kneading the powder coating composition include, for example, a heated roller machine, a heated kneader machine, an extruder, and the like. Examples of the pulverizer for pulverizing the powder coating composition after melt-kneading include impact pulverizers such as a hammer mill and a pin mill. As a classifier for classifying the powder coating composition after pulverization, for example, a vibrating sieve or the like can be mentioned.

[0066] The powder coating composition of the present embodiment can be applied to an object to be coated by a common coating method such as electrostatic coating or fluidized bed coating, and then heated and cured to form a coating film. The heating temperature (baking temperature) and time for forming the coating film can be appropriately set. For example, the heating temperature is usually set to be equal to or higher than the melting point of the thermoplastic resin.

[0067] Examples of substrates to which the powder coating composition of this embodiment can be applied include metals such as iron, zinc, tin, stainless steel, copper, aluminum, etc., inorganic materials such as glass, and substrates made of these metals or inorganic materials that have been subjected to a plaster treatment or a primer or undercoat coating as necessary.

[0068] The thickness of the coating film formed by the powder coating composition of this embodiment is not particularly limited, but is preferably 15 μm or more and 1 mm or less.

[0069] Before forming a coating film using the powder coating composition of this embodiment, a primer coating may be formed on the coating surface of the above-mentioned substrate (the surface to which the powder coating composition is applied) using a known primer coating.

[0070] According to the powder coating composition of this embodiment, since it contains the above-mentioned multi-stage copolymer for powder coating and a thermoplastic resin, it is possible to provide a powder coating composition capable of forming a coating film having good appearance and excellent toughness. EXAMPLES

[0071] The present invention will be specifically described below with reference to examples. Note that the present invention is not limited to these examples. Note that "parts" hereinafter refer to "parts by mass." The various measurement and evaluation methods are as follows.

[0072] [Measurement of volume average particle size of primary particles of multi-stage copolymer] The volume average particle size of the primary particles of the multistage copolymer was measured by the following method. The primary particle size of the dispersed particles in the dispersion liquid containing the multi-stage copolymer was measured using a laser diffraction / scattering type particle size distribution measuring device (product name: LA-960, manufactured by Horiba, Ltd.). The average value of the primary particle sizes was taken as the volume average particle size of the primary particles. The relative refractive index of the resin particles and the dispersion medium was all 1.12. Ion-exchanged water was used as the dispersion medium.

[0073] [Measurement of volume average particle size of secondary particles of multi-stage copolymer] The volume average particle size of the secondary particles of the multistage copolymer was measured by the following method. The secondary particle diameter of the dispersed particles in the dispersion liquid containing the multi-stage copolymer was measured using a laser diffraction / scattering type particle size distribution measuring device (product name: LA-960, manufactured by Horiba, Ltd.). The average value of the secondary particle diameters was taken as the volume average particle diameter of the secondary particles. The relative refractive index of the resin particles and the dispersion medium was all 1.12. Ion-exchanged water was used as the dispersion medium.

[0074] [Evaluation of the appearance of the coating] The appearance of the coating film obtained by applying and curing the powder coating composition was evaluated based on the leveling property of the coating film. The leveling property of the coating film was evaluated by the following method. The powder coating composition was sprayed onto a metal substrate (test piece; Q-panel QD46, thickness 0.5 mm) and cured at 200° C. for 10 minutes to form a coating film with a thickness of 100 μm. Thereafter, the long wavelength (LW) of the reflected light of the light irradiated onto the coating film was measured using a Microwave Scan AW-4824 (manufactured by BYK). The leveling property of the coating film was evaluated based on the obtained measured values ​​according to the following criteria. If LW was less than 50, the leveling property was considered to be good. LW50 or more: ×, LW40 to less than 50: 〇, LW less than 40: ◎

[0075] [Evaluation of coating toughness] The toughness of the coating film formed by applying and curing the powder coating composition was evaluated by the cupping resistance of the coating film. The cupping resistance of the coating film was evaluated by the following method. The powder coating composition was sprayed onto a metal substrate (test piece; Q-panel QD46, thickness 0.5 mm) and cured at 200° C. for 10 minutes to form a coating film with a thickness of 40 μm. The indentation depth of the coating was then measured according to ISO 1520 using a PCE-CPT manual cupping tester. From the obtained measured values, the cupping resistance was judged according to the following criteria: If the indentation depth was 2.5 mm or more, the cupping resistance was deemed good. Indentation depth less than 2.5mm: ×, Indentation depth 2.5mm to less than 4.0mm: 〇, Indentation depth 4.0mm or more: ◎

[0076] [Evaluation of the impact resistance of the coating] The toughness of the coating film formed by applying and curing the powder coating composition was evaluated by the impact resistance of the coating film. The impact resistance of the coating film was evaluated by the following method. The powder coating composition was sprayed onto a metal substrate (test piece; Q-panel QD46, thickness 0.5 mm) and cured at 200° C. for 10 minutes to form a coating film with a thickness of 40 μm. Thereafter, a ball drop test was carried out on the coating surface in accordance with ASTM D-2794, and the impact resistance of the coating was measured in inch-pounds (in-lbn). From the obtained measured values, the impact resistance was judged according to the following criteria: If the inch-pound value was 100 or more, the impact resistance was considered to be good. Less than 100 in-lbn: ×, 100 in-lbn to less than 140 in-lbn: 〇, 140 in-lbn or more: ◎

[0077] <Example 1> [Process (1-1)] In a 5-liter separable flask equipped with a thermometer, a nitrogen gas inlet tube, a stirring rod, a dropping funnel, and a cooling tube, 63.8 parts of deionized water was placed, and nitrogen gas was bubbled through for 30 minutes to replace the dissolved oxygen in the deionized water. Next, the nitrogen gas flow was stopped, and the temperature was raised to 80° C. while stirring at 200 rpm. Then, when the temperature inside the separable flask reached 80°C, 2.96 parts of methyl methacrylate, 1.97 parts of n-butyl acrylate, 0.19 parts of allyl methacrylate, and 0.03 parts of 1,3-butylene glycol dimethacrylate were added all at once, and then 0.05 parts of potassium persulfate and 2.38 parts of deionized water were added. The mixture was then held for 60 minutes to obtain a latex containing polymer (A) particles.

[0078] [Process (1-2)] To the latex obtained in the step (1-1), 0.04 parts of PELLEX OT-P, 0.05 parts of potassium persulfate, and 4 parts of deionized water were added, and 75.1 parts of n-butyl acrylate, 2.85 parts of allyl methacrylate, 1.52 parts of 1,3-butylene glycol dimethacrylate, 0.75 parts of PELLEX OT-P, and 51.6 parts of deionized water were added dropwise over 180 minutes. Thereafter, the mixture was maintained for 1 hour to complete the polymerization, thereby obtaining a latex containing particles in which the polymer (B) was polymerized around the polymer (A).

[0079] [Process (1-3)] To the latex obtained in the step (1-2), 17.7 parts of methyl methacrylate, 0.35 parts of ethyl acrylate, 1.9 parts of 2-hydroxyethyl methacrylate, 0.20 parts of 1,3-butylene glycol dimethacrylate, 0.20 parts of PELLEX OT-P, and 15 parts of deionized water were added dropwise over 140 minutes. Thereafter, the mixture was maintained for 2 hours to complete the polymerization, thereby obtaining a latex containing a multi-stage copolymer in which polymer (C) was polymerized around particles made of polymer (A) and polymer (B).

[0080] [Process (2)] The latex obtained in the step (1-3) was spray-dried using a spray dryer (product name: L-8i type, manufactured by Okawara Chemical Engineering Co., Ltd.) under the conditions of inlet temperature / outlet temperature = 120 ° C. / 60 ° C. and a disk rotation speed of 20,000 rpm, to obtain a multi-stage copolymer (P-1). The volume average particle size of the primary particles of the multi-stage copolymer was 0.70 μm. The results are shown in Table 2. FIG. 1 shows the tan δ curve between −60° C. and 140° C. calculated by measuring the temperature dispersion of the dynamic viscoelasticity of the multi-stage copolymer. The Tg of each of the polymers (A), (B) and (C) was calculated using the formula (1) from the Tg of the homopolymers shown in Table 1 corresponding to the monomer units constituting each polymer.

[0081] <Example 2> A multi-stage copolymer (P-2) was obtained in the same manner as in Example 1, except that the monomer components constituting the monomer units constituting the polymer (A), polymer (B), and polymer (C) were in the mass ratio shown in Table 2. The results are shown in Table 2.

[0082] <Example 3> A multi-stage copolymer (P-3) was obtained in the same manner as in Example 1, except that the monomer components constituting the monomer units constituting the polymer (A), polymer (B), and polymer (C) were in the mass ratio shown in Table 2. The results are shown in Table 2.

[0083] <Example 4> A multi-stage copolymer (P-4) was obtained in the same manner as in Example 1, except that the monomer components constituting the monomer units constituting the polymer (A), polymer (B), and polymer (C) were in the mass ratio shown in Table 2. The results are shown in Table 2.

[0084] <Example 5> A multi-stage copolymer (P-5) was obtained in the same manner as in Example 1, except that the monomer components constituting the monomer units constituting the polymer (A), polymer (B), and polymer (C) were in the mass ratio shown in Table 2. The results are shown in Table 2.

[0085] <Example 6> A multi-stage copolymer (P-6) was obtained in the same manner as in Example 1, except that the monomer components constituting the monomer units constituting the polymer (A), polymer (B), and polymer (C) were in the mass ratio shown in Table 2. The results are shown in Table 2.

[0086] <Example 7> [Process (1-1)] In a 5-liter separable flask equipped with a thermometer, a nitrogen gas inlet tube, a stirring rod, a dropping funnel, and a cooling tube, 63.8 parts of deionized water was placed, and nitrogen gas was bubbled through for 30 minutes to replace the dissolved oxygen in the deionized water. Next, the nitrogen gas flow was stopped, and the temperature was raised to 80° C. while stirring at 200 rpm. Thereafter, when the temperature inside the separable flask reached 80°C, half of the monomer mixture solution consisting of 6.00 parts of methyl methacrylate, 4.00 parts of n-butyl acrylate, 0.39 parts of allyl methacrylate, and 0.05 parts of 1,3-butylene glycol dimethacrylate was added all at once, and further, 0.05 parts of potassium persulfate and 2.38 parts of deionized water were added, and the mixture was maintained for 60 minutes. Next, the remaining half of the above monomer mixture solution was added dropwise over 30 minutes. Thereafter, the mixture was maintained for 30 minutes to complete the polymerization, thereby obtaining a latex containing polymer (A) particles.

[0087] [Process (1-2)] To the latex obtained in the step (1-1), 0.04 parts of PELLEX OT-P, 0.05 parts of potassium persulfate, and 4 parts of deionized water were added, and 70.0 parts of n-butyl acrylate, 2.66 parts of allyl methacrylate, 1.42 parts of 1,3-butylene glycol dimethacrylate, 0.70 parts of PELLEX OT-P, and 48.1 parts of deionized water were added dropwise over 180 minutes. Thereafter, the mixture was maintained for 1 hour to complete the polymerization, thereby obtaining a latex containing particles in which the polymer (B) was polymerized around the polymer (A).

[0088] [Process (1-3)] To the latex obtained in the step (1-2), 17.7 parts of methyl methacrylate, 0.35 parts of ethyl acrylate, 1.9 parts of 2-hydroxyethyl methacrylate, 0.20 parts of 1,3-butylene glycol dimethacrylate, 0.20 parts of PELLEX OT-P, and 15 parts of deionized water were added dropwise over 140 minutes. Thereafter, the mixture was maintained for 2 hours to complete the polymerization, thereby obtaining a latex containing a multi-stage copolymer in which polymer (C) was polymerized around particles made of polymer (A) and polymer (B).

[0089] [Process (2)] The latex obtained in step (1-3) was spray-dried to obtain a multi-stage copolymer (P-8) in the same manner as in Example 1. The results are shown in Table 2.

[0090] <Comparative Example 1> A multi-stage copolymer (P-8) was obtained in the same manner as in Example 1, except that the monomer components constituting the monomer units constituting the polymer (A), polymer (B), and polymer (C) were in the mass ratio shown in Table 2. The results are shown in Table 2.

[0091] [Table 2]

[0092] The compounds in Table 2 are as follows: "MMA": Methyl methacrylate (manufactured by Mitsubishi Chemical Corporation) "n-BA": n-butyl acrylate (manufactured by Mitsubishi Chemical Corporation) "AMA": Allyl methacrylate (manufactured by Mitsubishi Chemical Corporation) "BDMA": 1,3-butylene glycol dimethacrylate (manufactured by Mitsubishi Chemical Corporation) "EA": Ethyl acrylate (manufactured by Mitsubishi Chemical Corporation) 2-HEMA: 2-hydroxyethyl methacrylate (Mitsubishi Chemical) "MAA": Metallurgic acid (manufactured by Mitsubishi Chemical Corporation)

[0093] <Example 8> The components of the powder coating composition are as follows: Polyester resin: SP-6400 (Sun Polymer International) Hardener: Triglycidyl isocyanurate (TGIC) (Aalchem) Leveling agent: Resiflow P-67 (Estron Chemical) Defoamer: Benzoin (Estron Chemical) Pigment: TiPure R960 (Venator) Toughening agent: Multi-stage copolymer (P-1)

[0094] 61.4 parts of SP-6400, 4.6 parts of TGIC, 1 part of Resiflow P-67, 0.5 parts of Benzoin, 30 parts of TiPure R960, and 2.5 parts of multi-stage copolymer (P-1) were premixed in a Vitamix for 8 seconds. Thereafter, the pre-mixed mixture was melt-kneaded in a twin-screw extruder APV 19 mm (set at 100° C., screw speed 500 rpm, chill roll 18 rpm). The melt-kneaded mixture was then pulverized in a strand mill and sieved through a 140 mesh sieve to obtain a powder coating composition. The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0095] <Example 9> A powder coating composition was obtained in the same manner as in Example 8, except that the multi-stage copolymer (P-2) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0096] <Example 10> A powder coating composition was obtained in the same manner as in Example 8, except that the multi-stage copolymer (P-3) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0097] <Example 11> A powder coating composition was obtained in the same manner as in Example 8, except that the multi-stage copolymer (P-4) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0098] <Example 12> A powder coating composition was obtained in the same manner as in Example 8, except that the multi-stage copolymer (P-5) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0099] <Example 13> A powder coating composition was obtained in the same manner as in Example 8, except that the multi-stage copolymer (P-6) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0100] <Example 14> A powder coating composition was obtained in the same manner as in Example 8, except that the multi-stage copolymer (P-7) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0101] <Comparative Example 2> A powder coating composition was obtained in the same manner as in Example 2, except that the multi-stage copolymer (P-8) was used instead of the multi-stage copolymer (P-1). The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0102] <Comparative Example 3> 63.7 parts of SP-6400, 4.8 parts of TGIC, 1 part of Resiflow P-67, 0.5 parts of Benzoin, and 30 parts of TiPure R960 were premixed in a Vitamix for 8 seconds. Thereafter, the pre-mixed mixture was melt-kneaded in a twin-screw extruder APV 19 mm (set at 100° C., screw speed 500 rpm, chill roll 18 rpm). The melt-kneaded mixture was then pulverized in a strand mill and sieved through a 140 mesh sieve to obtain a powder coating composition. The obtained powder coating composition was used to form a coating film, and the coating film was evaluated for leveling property, cupping resistance and impact resistance. The results are shown in Table 3.

[0103] [Table 3] [Industrial Applicability]

[0104] INDUSTRIAL APPLICABILITY The multistage copolymer for powder coating of the present invention can provide a powder coating composition capable of forming a coating film having good appearance and excellent toughness, and therefore can be suitably used for outdoor applications such as road materials and building materials.

Claims

1. A multi-stage copolymer for powder coating, comprising at least three polymer components: a first stage polymer (A), a second stage polymer (B), and a third stage polymer (C), A powder coating composition comprising: a multi-stage copolymer for powder coating, the polymer (A) having a glass transition temperature of -15°C or higher, the polymer (B) having a glass transition temperature of -20°C or lower, and the polymer (C) having a glass transition temperature of 60°C or higher, the multi-stage copolymer for powder coating containing the polymer (A) in an amount of 1% by mass or more and 30% by mass or less when the total amount of the multi-stage copolymer for powder coating is taken as 100% by mass; and a thermoplastic resin which is a polyester.

2. A multi-stage copolymer for powder coating comprising at least an inner layer, an intermediate layer and an outer layer, the inner layer comprises a polymer (A) having a glass transition temperature of −15° C. or higher, the intermediate layer contains a polymer (B) having a glass transition temperature of −20° C. or lower, The outer layer contains a polymer (C) having a glass transition temperature of 60° C. or higher, A powder coating composition comprising: a multi-stage copolymer for powder coating, the multi-stage copolymer for powder coating containing 2% by mass or more and 20% by mass or less of the polymer (A) when the total amount of the multi-stage copolymer for powder coating is taken as 100% by mass; and a thermoplastic resin which is a polyester.

3. 3. The powder coating composition according to claim 1 or 2, comprising: the polymer (B) obtained by polymerizing a monomer mixture in the presence of the polymer (A); and the polymer (C) obtained by polymerizing a monomer mixture in the presence of a polymer containing the polymer (A) and the polymer (B).

4. A multi-stage copolymer for powder coating, comprising at least three polymer components: a polymer (A), a polymer (B), and a polymer (C), 3. A powder coating composition comprising the multi-stage copolymer for powder coating according to claim 1 or 2, wherein at least two peaks are present in a tan δ curve between -60°C and 140°C in a temperature dispersion measurement of dynamic viscoelasticity of the multi-stage copolymer for powder coating, and a thermoplastic resin which is a polyester.

5. The powder coating composition according to any one of claims 1 to 4, wherein the polymer (A) contains 35% by mass or more and 99.5% by mass or less of methyl methacrylate units and 0.5% by mass or more and 5% by mass or less of a polyfunctional monomer, when the total amount of monomer units in the polymer (A) is taken as 100% by mass.

6. 6. The powder coating composition according to claim 1, wherein the polymer (B) contains 70% by mass or more and 99.5% by mass or less of alkyl (meth)acrylate units having an alkyl group with 4 to 8 carbon atoms, and 0.5% by mass or more and 5% by mass or less of a polyfunctional monomer, when the total amount of monomer units in the polymer (B) is taken as 100% by mass.

7. The powder coating composition according to any one of claims 1 to 6, wherein the polymer (C) contains 70 mass% or more and 100 mass% or less of methyl methacrylate units, when the total amount of monomer units in the polymer (C) is taken as 100 mass%.

8. A powder coating composition described in any one of claims 1 to 7, wherein the volume average particle diameter of the primary particles of the multistage copolymer for powder coating is 0.1 μm or more and 10 μm or less.

9. A powder coating composition described in any one of claims 1 to 8, wherein the volume average particle diameter of secondary particles of the multistage copolymer for powder coating is 1 μm or more and 500 μm or less.

10. The powder coating composition according to any one of claims 1 to 9, wherein the powder coating composition contains 1 mass% or more and 30 mass% or less of the polymer (A), 31 mass% or more and 94 mass% or less of the polymer (B), and 5 mass% or more and 39 mass% or less of the polymer (C), when the total of the polymer (A), the polymer (B), and the polymer (C) is 100 mass%.

11. A method for producing the powder coating composition according to any one of claims 1 to 10, comprising the steps of: a step (1) of polymerizing a first monomer mixture for constituting a polymer (A) to obtain a first dispersion containing the polymer (A), then dropping a second monomer mixture for constituting a polymer (B) into the first dispersion to polymerize the second monomer mixture to obtain a second dispersion containing the polymer (A) and the polymer (B), and further dropping a third monomer mixture for constituting a polymer (C) into the second dispersion to polymerize the third monomer mixture to obtain a third dispersion containing a multistage copolymer containing the polymer (A), the polymer (B), and the polymer (C); and (2) spray-drying the third dispersion to obtain a powder containing the multistage copolymer.

12. The powder coating composition according to any one of claims 1 to 10, wherein the content of the multi-stage copolymer for powder coating is 1 mass% or more and 20 mass% or less, when the total amount of the powder coating composition is 100 mass%.

Citation Information

Patent Citations

  • JP1973055233A

  • Powder coating composition

    JP1998259323A

  • Multilayer-structured acrylic polymer and a metacrylic resin composition using the same

    JP1998338723A

  • Powder coating composition

    JP2000001633A

  • Thermosetting powdery paint composition

    JP2002173637A

Cited By

  • Multistage copolymer for powder coating material, production method therefor, and powder coating composition

    JP2024109853A